Implementation of extracurricular to develop a confident character for students in elementary schools - Eka Ratna Putri; Dea Mustika (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2024)
Self-confidence is an essential part of student personality development. Most students always have low self-confidence due to many factors, and to overcome this, efforts need to be made, one of these efforts being extracurricular activities. This study's background is to see how Muhadharah extracurricular activities can shape students' self-confidence. This research uses a qualitative approach with collection techniques through documentation studies from scientific sources, interviews with three participants, and observation of Muhadharah activities. Data analysis techniques use data reduction, presentation, and conclusion drawing and verification. Data validity uses triangulation techniques of sources, techniques, and time. The results showed that infrastructure facilities, activity schedules that do not collide with other activities, and sufficient funds support student participants in Muhadharah extracurricular activities. This activity trains students to perform and speak in public to form a brave and confident mentality in each of these students. AbstrakKepercayaan diri menjadi bagian yang sangat penting bagi perkembangan kepribadian siswa. Nyatanya kebanyakan siswa selalu memiliki kepercayaan diri yang rendah yang disebabkan oleh banyak faktor, dan untuk mengatasinya perlu dilakukan upaya, salah satu upaya tersebut yakni dengan melaksanakan kegiatan ekstrakurikuler. Hal itu melatarbelakangi penelitian ini dengan tujuan untuk melihat bagaimana kegiatan ekstrakurikuler Muhadharah mampu membentuk sikap percaya diri pada siswa. Penelitian ini menggunakan pendekatan kualitatif dengan teknik pengumpulan melalui studi dokumentasi dari sumber-sumber ilmiah, wawancara bersama tiga partisipan, observasi kegiatan Muhadharah. Teknik analisis data menggunakan reduksi data, penyajian data, dan penarikan kesimpulan serta verifikasi. Keabsahan data menggunakan teknik triangulasi sumber, teknik, dan waktu. Hasil penelitian menunjukkan bahwa sarana prasarana, jadwal kegiatan yang tidak bertabrakan dengan kegiatan lain, dan dana yang mencukupi mendukung partisipan siswa dalam ekstrakurikuler Muhadharah. Kegiatan ini melatih siswa untuk tampil dan berbicara di depan umum sehingga membentuk mental berani dan percaya diri dalam diri masing-masing siswa tersebut.Kata Kunci: ekstrakurikuler; karakter percaya diri; pembinaan